2011
DOI: 10.1590/s1516-35982011001100042
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Fourier Transform Infrared spectroscopy to determine adulterants in raw milk

Abstract: -The objective of this study was to develop calibrations to determine the concentration of some milk adulterants by using the automated methodology of Fourier Transform Infrared (FTIR). For construction of calibrations, samples were collected from 100 farms in the states of São Paulo and Minas Gerais. Samples were tainted with three different adulterants commonly used in the adulteration of raw milk: sodium bicarbonate (SB), sodium citrate (SC) and cheese whey (W).Each adulterant was used at three different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The milk scandal in 2008 led to the development of NIRS methods for the detection of melamine and other untargeted adulterants (Holroyd, ). Several studies have reported the use of fast and reliable methodologies mainly based on NIR and Fourier transform (FT)‐IR techniques to identify the presence of adulterants in milk such as melamine (Fernández Pierna et al ., ; Chen et al ., ), urea (Jha et al ., ; Khan et al ., ), sodium bicarbonate and sodium citrate in milk (Cassoli et al ., ). Comparison of the NIR fingerprint of milk samples to reference standard samples using multivariate analysis may be used to identify adulterants if present.…”
Section: Application Of Pat In Cheese Manufacturementioning
confidence: 97%
“…The milk scandal in 2008 led to the development of NIRS methods for the detection of melamine and other untargeted adulterants (Holroyd, ). Several studies have reported the use of fast and reliable methodologies mainly based on NIR and Fourier transform (FT)‐IR techniques to identify the presence of adulterants in milk such as melamine (Fernández Pierna et al ., ; Chen et al ., ), urea (Jha et al ., ; Khan et al ., ), sodium bicarbonate and sodium citrate in milk (Cassoli et al ., ). Comparison of the NIR fingerprint of milk samples to reference standard samples using multivariate analysis may be used to identify adulterants if present.…”
Section: Application Of Pat In Cheese Manufacturementioning
confidence: 97%
“…has been employed for the rapid detection and quantification of several adulterants in milk (Cassoli et al . ; Santos et al . ; Jaiswal et al .…”
Section: Introductionmentioning
confidence: 99%
“…Attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR) along with chemometrics [use of multivariate statistics such as principal component analysis (PCA), and partial least square (PLS), to address problems in chemistry, biochemistry, etc.] has been employed for the rapid detection and quantification of several adulterants in milk (Cassoli et al 2011;Santos et al 2013;Jaiswal et al 2015, Jha et al 2016, Jaiswal et al 2017. It has also been used to detect and characterise adulteration of edible oils with cheaper oils such as SO (Gurdeniz and Ozen 2009;Che Man et al 2010;Liang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of using spectroscopy for the quantitative determination of oleic acid in sunflower seeds has not been studied yet, although the NIRS has been successfully used to determine diverse compounds in numerous foods and industrial crops such as sesame, soybean, perilla and peanut, sunflower, rice, maize, and sweet potato [3]. The content of oleic acid in the form of glycerol esters (oleates) in different varieties of sunflower varies from 20 to 90 % and determines the nutritional value of sunflower oil [4].…”
Section: Introductionmentioning
confidence: 99%